Assessing the impacts of different crop rotations on groundwater level using MODFLOW in a dry, Barind area of Bangladesh. Issue 3 (14th March 2023) - Ali, M. H.; Biswas, P.; Zaman, M. H.; Islam, M. A.
Abstract: The lowering of the groundwater table caused by increased groundwater use in the dry, Barind region has prompted sustainability concerns. In this study, water-table (WT) scenarios were simulated by the MODFLOW model under different crop rotations in Barind, a dry region of Bangladesh, to examine the effects of crop rotations on groundwater level. The studied crop rotations and recharge conditions were: with existing cropping pattern; 100, 30 and 50% of present Boro rice is replaced by Aus rice; existing cropping pattern, but with reduced recharge to 90 and 80% of present recharge. A calibrated MODFLOW model was used to develop WT scenarios. According to the modeling results, the declination of WT will be lessened and the situation with regard to WT will therefore be improved with the gradual substitution of Boro by Aus and Rabi (30, 50 and 100%). The simulated WT scenario will be useful for policymakers to set policies about cropping patterns or groundwater withdrawal amounts targeting the area's long-term sustainability of groundwater. HIGHLIGHTS: Sustainable agricultural production in the Barind area is under threat due to unsustainable groundwater use. A calibrated MODFLOW model was used to predict the water-table (WT) under different cropping patterns. With the gradual substitution of Boro rice by Aus rice (e.g. 30%, 50%, and 100%), the situation for WT will be improved. The simulated WT scenario will therefore be useful for the policymakers. Graphical Abstract